Diseño conceptual de un biodigestor a partir de estiércol vacuno y avícola, producido en la finca El Guarumal, para la obtención de biogás (2018)
This project, developed in order to solve the lack of biogas at Finca El Guarumal, takes place in three experimental phases. The first consists of identifying the environmental conditions of the area through a preliminary design and the second involves the simulation of a solar collector to stabilize the process. In the third phase, the quantification of the biogas produced is carried out, and according to the results obtained in the latter, and the availability of waste given on the farm, cow manure is chosen as biomass and a design of the 250 L, taking into account the models of biodigesters found in the literature and the environmental conditions mainly, which according to the monitoring and records that are carried out for 90 days, require the use of a heating medium that allows stability of the process through its 4 stages (hydrolysis, acidogenesis, acetogenesis and methanogenesis) favoring the production of biogas results, for which the use of a homemade solar collector is proposed as a heating system in order to stabilize the operating conditions, especially the temperature. Similarly, in the proposed system, a medium-scale CSTR type biodigestor (pilot scale) is proposed, which fulfills the function of homogenizing the mixture, preventing the solids from decanting, allowing a greater contact between the mixture and the solids. microorganisms responsible for digesting the substrate and metabolizing it. Finally, a financial analysis of the project related the production of biogas with the equivalence of that production in profits or money saved by purchase of propane gas.